MEMBACA VISUAL MOTIF BATIK SEMARANGAN WARAK NGENDOG - Mursidah; Amin Sulistiyowati (Canthing, 2022)
Batik Semarangan has a variety of motives, including architectural motifs (Lawang Sewu, Tugu Muda, Sam Po Kong, and others) and floral fauna motifs (asem, tendrils, fish, etc.). One of batik Semarangan's unique and interesting motifs is Warak Ngendog's motif. Visualization of Warak Ngendog motif is made by referring to the mythological animal of Semarang belief. This journal will discuss the visual motives of Warak Ngendog through the semiotic viewpoint. This viewpoint sees batik motifs not merely images, but as cultural texts in which operate marking practices that lead to the method of reading batik motifs as a text. With this point of view Warak Ngendog's motives will be analyzed by traces of visual detail, how to form visual constructs, and to track his social history. Keyword: Batik Semarang, Warak Ngendog, Signs, Semiotic.